Internalisasi Nilai Religius dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan di Sekolah Daerah Tertinggal - Hendra Hendra; Junaidi Indrawadi; Maria Montessori (Universitas Negeri Medan, 2019)
This study aims to determine the process of internalizing religious values in learning Civic and Pancasila Education in underdeveloped regional schools. This research was conducted at Madrasah Tsanawiyah Negeri (MTsN) 1 Mentawai Islands because geographically Madrasah Tsanawiyah Negeri (MTsN) 1 Mentawai Islands is located in Mentawai Islands Regency as one of the underdeveloped areas in accordance with Presidential Regulation No. 131 of 2015 concerning Determination of Underdeveloped Regions 2015-2019. This study uses a qualitative approach to reveal how the process of internalizing religious values in learning Civic and Pancasila Education on Madrasah Tsanawiyah Negeri (MTsN) 1 Mentawai Islands. Data was obtained through observation, interviews, FGD (focus group discussion) and documentation studies. The results of the study show: 1) religious values have been internalized in the Civic and Pancasila Education Lesson Plan, 2) the teachers only limited to delivering religious values and have not invited students to think critically about religious values, 3) teachers have not evaluated learning that internalized religious values. Through this research the teacher is expected to be able to develop a model of internalization of religious values in the learning of Civic and Pancasila Education in underdeveloped area schools which includes planning, implementing and evaluating the learning of Civic and Pancasila